The Role of Operational Efficiency on Islamic Commercial Banks - Nabhan, Faqih; Widyaningsih, Ayu (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The study aims to analyze the effect of Fee-Based Income (non-interest income) and the Capital Adequacy Ratio on Profitability with an Efficiency bank as an intervening variable. The research object was a Sharia commercial bank registered in OJK from 2010 to 2019 with a sample of 11 banks. This type of research is quantitative research. Sampling was carried out by the purposive sampling method. The analysis tool used is multiple linear regression and analysis path (path analysis) using SPSS version 21 software. The study showed a positive and significant influence on Fee-Based Income and profitability. While the Fee-Based Income has a substantial effect on the operational efficiency ratio (OER), and the Capital Adequacy Ratio has a negative and significant effect on OER. The results of the path analysis showed that the bank efficiency (OER) was unable to mediate the influence of fee-based income on profitability but was able to negotiate the impact of the capital adequacy ratio on profitability in Islamic commercial banks from 2010 to 2019.